Gli investimenti stranieri nel Nord Africa in prospettiva storica : il caso della Tunisia - (:unkn) unknown (My University, 2001)
The research aims at an analysis of foreign investment in North Africa in historical perspective with particular reference to the trend of foreign direct investment in the manufacturing industry in Tunisia. The historical reasons that determine foreign investment in Tunisia will be considered in the first part of the study and relate mainly to the economic structure of the pre-colonial period and the experience of colonialism. In the central part of the research will be considered in the economic environment of the North African countries for foreign investment, euromaghrebine relations, bilateral relations between the countries of North Africa and the various incentive policies for investment. In the last part instead will be analyzed the trend in investment flows to the countries of North Africa with particular reference to the case of Tunisia and will present the results of a field study carried out on a limited sample of foreign companies operating in Tunisia.
Keywords: African Research